A frequency domain extraction procedure of low-pass equivalent behavioural models of microwave PAs - Siviero, C.
This paper reports on a novel extraction procedure of low-pass equivalent behavioral models of microwave power amplifiers. The proposed approach is based on the use of the discrete-time Volterra Series model and on the complex envelope of a multisine as stimulus. The model extraction procedure is formulated using an alternative orthogonal model representation in the frequency domain, providing a methodology which successfully leads to an optimal model identification not affected by the ill-conditioning of typical learning methods. © 2006 EuMA.